The correlations among motivation, self-confidence, and speaking ability of the eighth grade students - Suliyati Suliyati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aimed to determine correlation among motivation, self-confidence and speaking ability at the state islamic junior high schools in Musi Banyuasin. The research was conducted correlation research design. This study’s population comprised eighth grade studetns of junior high schools in Musi Banyuasin, sampling through a stratified random sampling of 50 students. Data collection techniques used include questionnaire and test. Based on the study results, the data showed that (1) correlation value of 0.885; (2) there is not any significant correlation between self-confidence and speaking ability with a correlation value of 0.623; (3) there is a significant correlation between motivation and self-confidence with a correlation value of 0.001 (4) there is simultaneous correlation among motivation and self-confidence with speaking ability with correlation value 0.883, with percentage of 0.5%. Whereas relation 99.5% is determined by other factors not mentioned in the study.